Effects of dietary chromium picolinate supplementation on serum and tissue mineral contents of laying Japanese quails - Şahin, Kazım; Şahin, Nurhan; Küçük, Ömer (Wiley-Liss, 2002)
This experiment was conducted to evaluate the effects of chromium (chromium picolinate, CrPic) on serum and tissue concentrations of Cr, Zn, Cu, Fe, and Mg of laying Japanese quails (Coturnix colurnix japonica). One hundred fifty laying Japanese quails (45 days old) were divided into five groups, 30 quails per group. The laying quails were fed either the control diet containing 1,285.96 mug of Cr/kg of diet or the control diet supplemented with 200, 400, 800, or 1,200 mug of Cr/kg of diet. Increasing dietary chromium supplementation linearly increased serum chromium and zinc concentrations (P = 0.01) but linearly decreased (P = 0.01) copper serum concentrations. Serum iron and magnesium concentrations did not change (P > 0.10) as dietary chromium supplementation increased. Similar response to Cr supplementation was also observed in tissue mineral concentrations. Liver, longissimus muscle, and kidney chromium and zinc concentrations linearly increased (P = 0.01), whereas copper concentrations linearly decreased (P = 0.01) as dietary chromium supplementation increased. Also, liver, longissimus muscle, and kidney iron and magnesium concentrations did not change (P > 0.10) as dietary chromium supplementation increased. The results of present study conclude that supplemental chromium to the diet of Japanese quails influences serum and tissue Cr, Zn, and Cu concentrations, thus most probably functions of the organs as well as the welfare of Japanese quails.
Keywords: Basal Diet; Glucose; Metabolism; Liver; Performance; Enhancement; Rabbits; Copper; Rats; Zinc